Hydrodynamics of Planing Monohull Watercraft - Vorus, William S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses the principles involved in the design and engineering of planing monohull power boats, with an emphasis on the theoretical fundamentals that readers need in order to be fully functional in marine design and engineering. Author William Vorus focuses on three topics: boat resistance, seaway response, and propulsion and explains the physical principles, mathematical details, and theoretical details that support physical understanding. In particular, he explains the approximations and simplifications in mathematics that lead to success in the applications of planing craft design engineering, and begins with the simplest configuration that embodies the basic physics. He leads readers, step-by-step, through the physical complications that occur, leading to a useful working knowledge of marine design and engineering. Included in the book are a wealth of examples that exemplify some of the most important naval architecture and marine engineering problems that challenge manyof today's engineers.
Conceptual Monohull Planing in Calm Water -- Slender-Body Hydrodynamics -- Time Domain Analysis -- Calm-Water Mechanics -- Planing in Sea Waves -- Data Requirements for Design -- An Engineering Approximation -- Appendix.
Keywords: Engineering design; Continuum mechanics; Mechanics, Applied; Engineering Design; Continuum Mechanics; Engineering Mechanics